Stress, trauma, and posttraumatic stress disorder in migrants: a comprehensive review - Bustamante, Lineth H.U. (Braz J Psychiatry, 2017)
OBJECTIVE: There is growing evidence supporting the association between migration and posttraumatic stress disorder (PTSD). Considering the growing population of migrants and the particularities of providing culturally sensitive mental health care for these persons, clinicians should be kept up to date with the latest information regarding this topic. The objective of this study was to critically review the literature regarding migration, trauma and PTSD, and mental health services. METHODS: The PubMed, SciELO, LILACS, and ISI Web of Science databases were searched for articles published in Portuguese, English, Spanish, or French, and indexed from inception to 2017. The following keywords were used: migration, mental health, mental health services, stress, posttraumatic stress disorder, and trauma. RESULTS: Migration is associated with specific stressors, mainly related to the migratory experience and to the necessary process of acculturation occurring in adaptation to the host country. These major stressors have potential consequences in many areas, including mental health. The prevalence of PTSD among migrants is very high (47%), especially among refugees, who experience it at nearly twice the rate of migrant workers. CONCLUSIONS: Mental health professionals must be trained to recognize and provide appropriate care for posttraumatic and/or stress-related disorders among migrants.